2008
DOI: 10.1088/0953-4075/41/9/095703
|View full text |Cite
|
Sign up to set email alerts
|

Stark effect of high-nhydrogen-like transitions: quasi-contiguous approximation

Abstract: Calculations of line shapes of highly excited (Rydberg) atoms and ions are important for many topics in plasma physics and astrophysics. However, the Stark broadening of the radiative transitions originating from high-n levels of hydrogen or hydrogen-like ions is rather complex, making the detailed calculations of their spectral structure very cumbersome. Here, we suggest a simple analytical method for an approximate calculation of such line shapes. The utility of the method is demonstrated in application to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 25 publications
1
60
0
1
Order By: Relevance
“…(3.51), not present in the original study [10], was empirically found to serve as a rough correction for the ∆n = 1 case; we remind the reader that the QC approximation was derived assuming ∆n ≫ 1). Static/dynamic Stark ratio:…”
Section: Spectroscopymentioning
confidence: 95%
See 1 more Smart Citation
“…(3.51), not present in the original study [10], was empirically found to serve as a rough correction for the ∆n = 1 case; we remind the reader that the QC approximation was derived assuming ∆n ≫ 1). Static/dynamic Stark ratio:…”
Section: Spectroscopymentioning
confidence: 95%
“…Typical Debye screening (plasma screening of a Coulomb field exerted by a probe charge at the distance of the Wigner-Seitz radius): The Stark broadening is calculated in the quasi-contiguous (QC) approximation [10], applicable to transitions between degenerate atomic levels. The method is summarized below.…”
Section: Spectroscopymentioning
confidence: 99%
“…Stambulchik and Maron [27] made some advances into approximate analytical calculations of the Stark widths of highly-excited hydrogen/deuterium lines. (They started within the CT, where the ion-dynamical effects are neglected, but then tried to take into account the ion dynamics in a rough approximation).…”
Section: /2 Ementioning
confidence: 99%
“…The Stark broadening is estimated 19 by quasicontiguous approximation 20 of the Holtsmark micro-field from the local electrons within the Debye radius, where the electron density is estimated by matching the quasicontiguous Stark width of the Lyman-a emission line from H atoms. A smaller electron density corresponds to a smaller Stark width, which results in narrower wings in the emission line profile and a sharper characteristic absorption dip in the center of the profile.…”
Section: à3mentioning
confidence: 99%